OPTIMIZATION OF DISTRIBUTION CHANNELS IN THE MARKETING OF SAVE AND ENVIRONMENTALLY FRIENDLY DETERGENTS (DELTAMAT) MSMEs IN CIMANGLID VILLAGE, BOGOR REGENCY - Sakti Brata Ismaya; Titus Indrajaya; Hammad Bawazir; Diva Yolanda Septa (International Journal of Economy, Education and Entrepreneurship, 2022)
The development of technology and industry makes people more honed and skilled in finding an added value in the products they produce. MSMEs, which are one of the pillars of the Indonesian economy, can present environmentally friendly products and replace other similar products. Cleaners, such as soap and detergent, are one of the people's needs that are routinely purchased. Detergent is a further innovation from soap because it has better washing power and is not affected by the mineral content in the water. The ability of producers, especially those who are serious about producing environmentally friendly products, must be balanced with appropriate marketing strategies. One that can use is the distribution channel to bring the product closer to the final consumer. With efforts to produce quality products and balanced with appropriate marketing strategies, MSME products can also grow and compete with other products that are already present and dominate the market